RANCANG BANGUN SISTEM INFORMASI E-COMMERCE PADA UMKM "MONDAY TO FRIDAY" BERBASIS WEBSITE MENGGUNAKAN METODE AGILE - Muhammad Idzhar Abisina (2023)
"Monday to Friday" MSME is an MSME in Jakarta, this MSME sells women's clothing which they design themselves. This MSME is still conventional and have not utilized technology in their business processes, which has resulted in a reduced level of sales due to a lack of extensive marketing. It was noted in the sales report, that "Monday to Friday" MSME experienced a decrease in sales of 38.78% by comparing the total turnover in November 2021 with December 2022. In addition, the MSMEs also felt that they were not effective in recording transactions because they were still done manually which has the risk of errors or data loss so that MSME business processes become ineffective and inefficient. This study aims to design a website-based e-commerce information system to expand marketing reach and digitize ongoing business processes. In this study the authors used the agile method and also used the PHP programming language with the codeigniter framework and supported by the MySQL database. The author uses the agile method because this method is very adaptable to circumstances and does not require too many resources. From the results of the study it was found that designing e-commerce websites makes it easier for MSMEs to provide services to buyers, expand marketing reach, and simplify the process of recording sales reports